Effects of Different Oligosaccharides on Growth Performance and Intestinal Function in Broilers - Chang, Ling; Ding, Yanan; Wang, Yushi; Song, Zehe; Li, Fei; He, Xi; Zhang, Haihan (Frontiers in Veterinary Science, 2022)
Objective This study was conducted to investigate the effects of different oligosaccharides on the growth performance and intestinal function in broilers. Methods A total of 360 1-day-old yellow-feather chickens were randomly divided into 5 groups and fed with a basal diet supplemented with 50 mg/kg chlortetracycline (ANT), 3 g/kg isomalto-oligosaccharide (IMO), 3 g/kg raffinose oligosaccharide (RFO), and 30 mg/kg chitooligosaccharide (COS). The experiment lasted for 56 days, with 1–28 days as the starter phase and 29–56 days as the grower phase. Results The results showed that dietary supplementation with RFO and COS significantly improved average daily gain (ADG) and average daily feed intake (ADFI) (p < 0.05). Relative to the control group, diets supplemented with oligosaccharides dramatically increased the level of serum IgM (RFO, COS), T-SOD (COS), and GSH-Px (IMO and RFO) and the expression of ZO-1(IMO) and claudin-1 (RFO) (p < 0.05). Adding antibiotics or oligosaccharides to the diet could remarkedly increase the villus height and villus height (VH)/crypt depth (CD) ratio of each group (p < 0.05). Through the ileum α-diversity analysis and comparison of OTU number in each group showed that the microbial richness of the IMO group increased in the starter phase, and that of the RFO and CSO group increased in the grower phase. Additionally, compared with the control group, IMO supplementation increased the level of ileum sIgA (p < 0.05) and the content of valeric acid (p < 0.05) in the cecum. Conclusions In summary, the addition of oligosaccharides in diet can improve the immune function and antioxidant capacity and improve intestinal health of broilers.